A prospective study of 50 cases of patella fractures treated with different modalities - V. Chawda, Rajesh; Tank, Parag M.; Patel, Vijay J.; Shah, Yash S. (International Journal of Research in Orthopaedics, 2018)
Background: Fractures of patella account for 1% of all skeletal injuries. There is no universal accepted treatment for patellar fractures. After a fracture of the patella, the best results are obtained by accurate reduction and stable internal fixation. Partial or total patellectomy is generally indicated when the patella is so severely comminuted that an accurate reduction and reconstruction of the retropatellar joint surface cannot be achieved. Methods: The prospective study of 50 cases of patellar fractures was carried out at the department of orthopaedics for the period from May 2015 to December 2017. The maximum period of follow up was 18 months with a minimum period of follow up of 5 months (average 11.68 months). Operative treatment was done in patella fractures for more than 2 mm of articular displacement or 3 mm of fragment separation. Surgical options includes internal fixation with tension band wiring with k wire and partial patellectomy with extensor mechanism repair. Results: We have studied 50 patients where 7 cases were treated conservatively. In the present series 22 patients were treated with internal fixation out of which 13 patients had excellent results. 6 patients had good results. 21 patients were treated with partial patellectomy where 6 patients had excellent results, 11 patients had good and 4 patients had fair results. Conclusions: Patella should be preserved and Osteosynthesis whenever possible has better chance for excellent results. A good surgical technique, optimal operation room environment and judicious use of antibiotics will reduce the possibility of infection.